2005
DOI: 10.1093/carcin/bgi144
|View full text |Cite
|
Sign up to set email alerts
|

The functional polymorphism in the matrix metalloproteinase-7 promoter increases susceptibility to esophageal squamous cell carcinoma, gastric cardiac adenocarcinoma and non-small cell lung carcinoma

Abstract: An A to G transition at the 181 base pair position upstream of the transcription initiation site of the matrix metalloproteinase-7 (MMP-7) gene (-181A/G) may modify the development and progression of some diseases via influencing the transcription activity of the promoter. To assess the effects of the functional single nucleotide polymorphism on cancer susceptibility and progression, the MMP-7 -181A/G genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism analysis among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
106
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 37 publications
1
106
1
2
Order By: Relevance
“…Matrix metalloproteinase-7 À181A4G was the only polymorphism differently distributed among gastric carcinoma patients compared with control subjects: AA 43.0%, AG 46.8%, and GG 10.1% in patients vs AA 27.2%, AG 62.7% and GG 10.1% in controls (Po0.04; Table 2). Comparison of the genotype distribution of our Caucasian control subjects with those published on other mainly Asiatic control groups (Wollmer et al, 2002;Ghilardi et al, 2003;Krex et al, 2003;Miao et al, 2003;Wang et al, 2004;Zhou et al, 2004;Matsumura et al, 2005;Zhang et al, 2005) showed significant differences for MMP-2 À1306C4T , MMP-7 À181A4G , TIMP-1 372C4T and TIMP-2 À418G4C (Table 3). All the SNPs were evaluated for association with the clinicopathological parameters.…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…Matrix metalloproteinase-7 À181A4G was the only polymorphism differently distributed among gastric carcinoma patients compared with control subjects: AA 43.0%, AG 46.8%, and GG 10.1% in patients vs AA 27.2%, AG 62.7% and GG 10.1% in controls (Po0.04; Table 2). Comparison of the genotype distribution of our Caucasian control subjects with those published on other mainly Asiatic control groups (Wollmer et al, 2002;Ghilardi et al, 2003;Krex et al, 2003;Miao et al, 2003;Wang et al, 2004;Zhou et al, 2004;Matsumura et al, 2005;Zhang et al, 2005) showed significant differences for MMP-2 À1306C4T , MMP-7 À181A4G , TIMP-1 372C4T and TIMP-2 À418G4C (Table 3). All the SNPs were evaluated for association with the clinicopathological parameters.…”
Section: Resultsmentioning
confidence: 49%
“…The only SNP that was distributed significantly differently among gastric carcinoma patients compared to our control population was MMP-7 À181A4G , with more patients of the AA genotype than in controls. The latter was not expected from previous studies on gastrointestinal cancer (Ghilardi et al, 2003;Zhang et al, 2005) and is most likely caused by ethnic differences (Asiatic vs Caucasian; Table 3), disease localisation (gastric vs colon) and the relatively low number of patients included in the studies. In our study, the gastric cancer patients with the variant AG/GG genotype showed worse survival data than the AA patients (Table 4 and Figure 1B), although the difference did not fully reach statistical significance.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…15,29 MMP-7 is constitutively expressed in exocrine and mucosal epithelial cells in the skin, pancreas, liver, breast, intestine, and lung. In cancers of the colon, [30][31][32][33] esophagus, 34 stomach, [34][35][36] pancreas, 37 breast 38 and prostate, 39 increased MMP-7 expression is associated with tumor invasion, cancer progression, and poor prognosis. Two mechanisms may be responsible for the enhancement of cancer invasion and metastasis by MMP-7: direct effects of MMP-7 proteinase activity and indirect effects of MMP-7, such as activation of MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%